Colonettes, David Sassoon Clocktower - Ghosh, Ayan (2023)
During the 17th century, many architects studying in Italy got inspired by Palladio's work, and on returning to their home countries, they adopted the Palladian style, leading to its widespread popularity across Europe and North America. The style remained popular till the 19th century, later making way for Neo-Classical and Neo-Gothic styles.